Health technology assessment of paediatric medicines: European landscape, challenges and opportunities inside the conect4children project. Issue 12 (28th January 2022) - Moretti, Francesco; Ruiz, Fabrice; Bonifazi, Fedele; Pizzo, Elena; Kindblom, Jenny M.; ,
Abstract : The medicine development process is complex and requires time and effort to ensure safety, efficacy and quality. In paediatrics, this process is even more challenging, as it involves a subgroup of the population that already faces a considerable gap in the clinical evaluation of medicines and devices compared to the adult population. Moreover, access to therapies is heavily influenced by national health technology assessment (HTA) recommendations, which often form the basis for pricing and reimbursement decisions that affect the availability of effective treatments within the national health systems. Yet performing an HTA to assess the relative effectiveness and cost‐effectiveness of a new children's treatment has several non‐trivial implications, creating a critical issue for the paediatric population. In addition, the advent of innovative health technologies for children emphasises the need to empower the role of HTAs in paediatrics. This article aims at describing the most relevant elements of the drug development process in the paediatric field by focusing on the HTA. Particular attention will be paid to the factors that influence market access for new paediatric medicines and patients' access to treatment. The article will also highlight some central methodological challenges in conducting HTA in the paediatric field. Finally, the article will provide insight into how initiatives, such as conect4children, may subsequently reinforce HTA awareness in the paediatric community and strengthen collaborations through network mechanisms.